Driving among Adolescents with Autism Spectrum Disorder and Attention-Deficit Hyperactivity Disorder - Haley Bishop; Logan Boe; Despina Stavrinos; Jessica Mirman (Safety, 2018)
Over the past several decades there has been a surge of research on the contextual, biological, and psychological factors associated with transportation safety in adolescence. However, we know much less about the factors contributing to transportation safety among adolescents who do not follow a typical developmental trajectory. Adolescents with developmental disabilities (DD) such as Autism Spectrum Disorder (ASD) and Attention-Deficit/Hyperactivity Disorder (ADHD) have a wide range of behavioral and psychological deficits that may make the complex task of driving even more challenging. Because these adolescents often retain characteristic symptoms of their disorder into adulthood, it may impede their ability to achieve important milestones during the developmental transition from adolescent to adult. As the motivating force behind autonomous living and employment, the capacity for independent transportation is paramount to an adolescent’s overall success. This critical review will draw from the current body of literature on adolescent drivers with developmental disabilities to determine (1) areas of impairment; (2) safety risk factors; and (3) effective interventions for improving driving safety in this vulnerable population of adolescent drivers between the ages of 15–22. This review will also identify important unanswered research questions, and summarize the current state of the literature.